Modeling and Optimization of Hybrid Energy System for Rural Electrification in Isolated Region using HOMER - Md Mustafa Kamal, Imtiaz Ashraf (International Journal of Advanced Science and Technology, 2020)
Worldwide, millions of people not able to access a clean form of energy. In developing countries like India, energy poverty is the main issue in the growth and economic development of the rural population.  The microgrid is the best option to provide a reliable and cost-effective power supply in the rural area where grid extension is not possible. In the present work, economic and technological solutions of the electrification of the rural community investigated by forming the hybrid energy model by integrating the available energy resource in the vicinity. The proposed model consists of solar/diesel and battery systems for reliable electrification of an isolated rural community. The suggested framework investigated the remote rural community of Uttarakhand state of India, considering the cluster of the un-electrified village. Sensitivity analysis and size optimization performed by using HOMER software in ordered to meet the required electrical load of the rural area. The optimization model suggests the optimum model having the cost of energy (COE), Net present cost (NPC), maximum renewable fraction, and low carbon emission.